BICEPS FEMORI RESPONSE IN CERVICAL SPINAL CORD INJURY WHEN APPLYING TENSION TO THE SCIATIC NERVE - Jiménez Jiménez, S (Cuestiones de Fisioterapia, 2009)
Objective: it was evaluated the electromyographyc response of the biceps femori when increasing tension on the sciatic nerve, using the Slump test with little variations. Material and method: there was an eight healthy volunteers control group (Group I) and a three volunteers group with traumatic cervical spinal cord injury (Group II). Results: Six members of Group I (75 %) showed an electromyographyc response to the test and two of them (33 %) also showed electromyograpyc variations to cervical manoeuvres. Two members of Group II (66 %) showed a positive response to the test and both of them (100 %) suffered variations with cervical manoeuvres. It was obtained these quantitative differences to cervical manoeuvres and also qualitative differences. Group I responded tonically, while Group II showed a fast dissolution of the contraction. Conclusion: these results show the necessity of keep studying this field because of the clinical importance of the implications.